Integrating Cognitive Antecedents to UTAUT Model to Explain Adoption of Blockchain Technology Among Malaysian SMEs - Hamed Khazaei (Society of Visual Informatics, 2020)
Blockchain technology is gaining consideration more and more and will potentially revolutionize most of the industries. Bitcoin cryptocurrency which uses Blockchain platform, has even promoted this technology more. Blockchain is a decentralized source and encrypted database for storing transaction information. Instead of being dependent on a centralised mediator like bank, by using blockchain, parties can transfer fund promptly trough connected ledgers called blocks. Using this method transactions will significantly be more transparent for both parties. Consequently, transactions are performed based on the distributed trust among other blockchain users in the network. Blockchain will promote transparency in every industry, yet implementation of blockchain technology is still limited. This study focuses to study the possible factors affecting adoption of blockchain technology by focusing on literature review and using Unified Theory of Acceptance and Use of Technology as a theoretical basis.